Dancing through pregnancy: Activity guidelines for professional and recreational dancers - Sanders, S. G. (Journal of Dance Medicine & Science, 2008)
Over the past few years the benefits of exercise during pregnancy have become appreciated. Much attention has been given to common forms of exercise, such as aerobic dance, swimming, cycling and running. The effects of professional and recreational dance during pregnancy, such as ballet or flamenco, for example, have not been explored. Many studies, however, address issues relevant to dance. The purpose of this article is to delineate as clearly as possible what dance activities are safe and even possibly beneficial for the mother and her baby, as well as those activities and levels of exertion that should be avoided.